Performing improvisation on drum set during modern performance: preparation technique / Fahmi Radhi Norman - Norman, Fahmi Radhi (2013)
This study was carried out to determine the techniques used as a preparation in order to perform drum set improvisations during modem performances among drum set students in UiTM Shah Alam. A total of the respondents selected for this study are Forty (N=40) drum set students from Diploma and Degree from the Faculty of Music, UiTM, section 17, Shah Alam. A set of questionnaire was design to get a primary data from the respondents about their practice techniques as a preparation to learn drum set improvisations during modern performances. The overall findings of the study show that, the students prefer to attend class to learn from principal lecturer. The students also still face a main problem which is tend to get boring during practice and create improvisations on drum set during performances. Practice strategies which is important to the drum set students is always seeks help and opinion from lecturer and friends during practicing dmm set improvisations. In the final part for this report, the suggestion for future research have been included to get more accurate results and to the highest level off this study.